Macro- and Microvascular Outcomes in Patients with Type 2 Diabetes Treated with Rapid-Acting Insulin Analogues or Human Regular Insulin: a Retrospective Database Analysis - Rathmann, W.; Schloot, N. C.; Kostev, K.; Reaney, M.; Zagar, A. J.; Haupt, A. (Experimental and Clinical Endocrinology & Diabetes, 2014)
To investigate the risk of macro- and microvascular complications in patients with type 2 diabetes receiving rapid-acting insulin analogues (IA) or human regular insulin (HI).General practice diabetes patients with continuous prescription of any IA or HI for ≥3 years were selected from the German Disease Analyzer database (IMS Health). Logistic and Cox regression models were applied to analyze the incidence and time to onset of vascular outcomes (IA vs. HI).2764 patients on IA (insulin lispro, glulisine, aspart) and 4193 patients on HI were included (age, mean [SD]: 61.0 [11.3] and 64.7 [10.5] years, follow-up [Q1,Q3]: 4.6 [3.7,6.1] and 4.7 [3.7,5.9] years). No significant differences were detected between IA and HI regarding the incidence of vascular complications (OR [95%CI]: macrovascular 0.92 [0.72–1.18], microvascular 0.95 [0.77–1.17]) or regarding time to their onset, after adjustment for sex, age, comorbidities and time on IA/HI, or by propensity-score-based matching. However, in an additional short-term analysis (median [Q1,Q3] follow-up (IA 2.9 [1.2,4.6], HI 2.4 [0.8,4.4] years) of a larger sample (no continuous insulin treatment required) with more comorbidities, time to onset of macrovascular complications was significantly longer for AI than HI (HR 0.88 [0.81–0.97], p=0.009; microvascular complications: no difference).After long-term continuous treatment with IA or HI under real-life conditions, there was no different risk of macro- or microvascular complications, contradicting previous short-term analyses. Further prospective studies are needed to clarify whether selection bias may have been introduced by using strict entry criteria.
Keywords: diabetes; cardiovascular risk management; insulin